1996
DOI: 10.18174/njas.v44i4.538
|View full text |Cite
|
Sign up to set email alerts
|

Broomrape (Orobanche cernua) control before attachment to host through chemically or biologically manipulating seed germination

Abstract: Seven series of laboratory and glasshouse experiments were conducted to investigate different methods of testing and studying the effect of several chemicals, root exudates of germinating crop seeds, and their interactions on Orobanche cernua. Compared to experiments in an incubator, better results were obtained when seed germination was tested in the presence of seedlings of host plants under glasshouse conditions. GR24 at 0.1 and 1.0 mg kg-1 was the most effective in stimulating the germination of O. cernua … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The application of nitrogen fertilisers limited practical importance as a control measure for O. crenata (Dhanapal & Struik, 1996). However, the cost of this technique in pasture could be offset by increased yield.…”
Section: Soil Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of nitrogen fertilisers limited practical importance as a control measure for O. crenata (Dhanapal & Struik, 1996). However, the cost of this technique in pasture could be offset by increased yield.…”
Section: Soil Managementmentioning
confidence: 99%
“…for P. aegyptiaca , Egyptian clover ( Trifolium alexandrinum L.) for O. crenata , sunhemp ( Crotalaria juncea L.) and mung bean [ Vigna radiata (L.) Wilczek] for O. cernua Loefl. (Dhanapal & Struik, 1996). Fenugreek stimulates P. ramosa seed germination, but not the seeds of O. foetida Poir.…”
Section: Rotationmentioning
confidence: 99%
“…According to Aly (2007), Elzein & Kroschel (2003) reported that the application of germination stimulants to induce suicidal seed germination of parasitic weeds appears attractive for biosafety reasons; there is rapid soil decomposition and high biological activity at very low application rates. Compounds structurally related to strigolactone are potent synthetic germination stimulants for many Striga and Orobanche/Phelipanche species (Zwanenburg & Wigchert 1998;Wigchert et al 1999) but their usage in the field has not been practical up to now due to the high cost involved in their synthesis and also their instability in soils with high pH (Dhanapal & Struik 1996;Kroschel 2001;Lopez-Raez et al 2008). Therefore, detailed studies are needed to solve the issues about the cost and the formulation of the substances, which are affecting the efficiency and stability of them in the field conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Once broomrape seeds have ger minated, they must establish contact with the host roots rapidly in order to derive nu trients and water for further growth and development. This germination phase is a critical period in the life cycle of the parasite (Musselman & Press 1995;Dhanapal et al 1996). If broomrape seeds are stimulated to germinate in the absence of host plants, the parasite seedlings die because of lack of nutrition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation